PERILAKU MASYARAKAT TERHADAP KEBERSIHAN LINGKUNGAN DI DESA TANETE KECAMATAN MARITENGNGAE (Studi Tentang: Perilaku Membuang Sampah di Sungai) - Iisrianti Iisrianti; Sapri Sapri; Hariyanti Hamid (JIA: Jurnal Ilmiah Administrasi, 2021)
This study aims to determine the behavior of the community towards environmental cleanliness (rivers) and to determine the factors that influence community behavior towards environmental cleanliness (rivers) in Tanete Village, Maritengngae District. The research population was 40 people/person and the sample was 40 people/person. The sampling technique used is saturated sampling. This type of research is descriptive quantitative. Data collection techniques used are observation, library research, questionnaires or questionnaires and interviews. Data analysis techniques used statistics, linear regression and hypothesis testing. The results showed that the behavior of the people of Tanete Village 49.83% was not good in maintaining the cleanliness of the river environment, in terms of discipline 45.5% was not good, 52.5% was not good at responsibility and 51.5% was not good at mutual cooperation. . Based on SPSS data processing using a linear regression formula, internal factors 5.9% and external factors 2.6% affect people's behavior towards the cleanliness of the river environment in Tanete Village.